Cultural fusion theory: An alternative to acculturation. Issue 2 (3rd April 2017) - Croucher, Stephen M.; Kramer, Eric
ABSTRACT: This article lays out a theoretical framework for cultural fusion theory. This theory borrows from various theoretical frameworks to provide a more realistic description of the immigrant experience. Specifically, cultural fusion theory describes how newcomers acculturate into the dominant culture and maintain aspects of their minority culture, while at the same time the dominant or host culture also fuses aspects off the newcomer's culture into the dominant culture to create a fused intercultural identity. Boundary conditions, assumptions, axioms, and theorems are presented to define cultural fusion theory.